2017
DOI: 10.1111/crj.12726
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up of 1887 patients receiving tumor necrosis‐alpha antagonists: Tuberculin skin test conversion and tuberculosis risk

Abstract: Despite the high proportion of isoniazid prophylaxis, the incidence of tuberculosis in our patients receiving TNF-α antagonist was higher than the literature. Adalimumab treatment, male sex and previous tuberculosis disease history were found as risk factors for tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
1
15
0
1
Order By: Relevance
“…As in previous investigations, our study showed a high incidence of TB in patients with rheumatic diseases exposed to TNF inhibitors therapy: 735.29 per 100,000 exposed, approximately 18 times higher than that of the general population of the state of Rio Grande do Sul (39.5 per 100,000). [24]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in previous investigations, our study showed a high incidence of TB in patients with rheumatic diseases exposed to TNF inhibitors therapy: 735.29 per 100,000 exposed, approximately 18 times higher than that of the general population of the state of Rio Grande do Sul (39.5 per 100,000). [24]…”
Section: Discussionmentioning
confidence: 99%
“…[23] In patients given infliximab, risk could be up to 30 times greater than in the general population. [24,25]…”
Section: Introductionmentioning
confidence: 99%
“…The overall incidence (all diagnoses) was 423/100,000 PY. The use of adalimumab (9.5-fold increase), male gender (15.6-fold increase) and a history of TB (11.5fold increase) were indicated as risk factors for TB in the multivariate analysis [162] (2B). The other study is a casecontrol study in which 73 (52.1% patients with AS) cases of TB among anti-TNFα drug users were compared with 7695 (50.6% patients with AS) controls, namely, anti-TNFα drug users without TB.…”
Section: Does the Safety Of Biologics Differ In Patients With Axial Spa?mentioning
confidence: 99%
“…The majority of individuals with LTBIs remain asymptomatic during their lifetime, although 5%‐10% of them are at risk of TB reactivation . This is why an individual with LTBI is regarded as a potential reservoir of Mtb …”
Section: Introductionmentioning
confidence: 99%